Animate words facilitate noun–noun integration during an imagery task: an event-related potential study. Issue 10 (3rd July 2019) - Zhang, Jie; Li, Xiaohuan; Guo, Chunyan
Abstract : The animate–inanimate distinction is fundamental to understand our physical world and language processing. Previous studies have shown that animate nouns are more prone to be assigned the actor role and are easier to integrate with a verb than inanimate nouns. On the basis of these characteristics of animate nouns, this study aimed to investigate whether animate nouns could facilitate the noun–noun integration. Animate–inanimate noun pairs and inanimate–inanimate noun pairs were used in an imagery task. With electroencephalogram recording, participants were instructed to integrate the two unrelated nouns in each pair to form an interactive mental imagery. These results showed a larger P600 for the animate–inanimate pairs than the inanimate–inanimate pairs. As the P600 component reflects the integration process, specifically, the more elaborate the encoding, the larger the P600 amplitude. Thus, this larger P600 amplitude indicated that a more vivid mental imagery was formed when integrating an animate noun and an inanimate noun than integrating two inanimate nouns. Thus, these results suggest that animate nouns could facilitate the integration of two unrelated nouns during the imagery task.